Home Health Care and Hospice Use Among Medicare Beneficiaries With and Without a Diagnosis of Dementia - Kim, Hyosin Dawn; Duberstein, Paul R; Lin, Haiqun; Wu, Bei; Zafar, Anum; Jarrín, Olga F (Journal of palliative medicine, 2024)
Background: Home health care is a core benefit of Medicare and Medicaid insurance programs and includes services to improve health, maintain health, or slow health decline. Objective: To examine the relationship between home health care use during the last three years of life and hospice use in the last six months of life among Medicare beneficiaries with and without dementia. Design: Nationally representative retrospective cohort study. Setting/Subjects: Medicare beneficiaries with at least three years of continuous enrollment who died in 2019 in the United States ( n = 2,169,422). Measurements: The primary outcome was hospice use, and the secondary outcome was hospice duration. The independent variable was a composite of the presence and timing of home health care initiation during the last three years of life. Results: Home health care was used by 46.4% of Medicare beneficiaries and hospice care was used by 53.1% of beneficiaries, with 28.3% using both. Compared with beneficiaries who did not use home health care, those who started home health care before the last year of life (odds ratio [OR] = 1.57, 95% confidence interval [CI] = 1.56–1.58) or during the last year of life (OR = 1.75, 95% CI = 1.74–1.77) were more likely to use hospice. The effects were stronger in those without a diagnosis of dementia (OR = 1.92, 95% CI = 1.90–1.94) compared with those without a dementia diagnosis (OR = 1.34, 95% CI = 1.32–1.35) who started home health in the final year of life. Conclusions: Receiving home health care in the final years of life is associated with increased hospice use at the end-of-life in Medicare beneficiaries with and without a dementia diagnosis.